MODEL ROBOT TROLI OBJECT FOLLOWER MENGGUNAKAN PIXY CMUCAM5 BERBASIS ARDUINO UNO 328P - Hadian Adam Herman; Andi Chairunnas (Ilmu Komputer, FMIPA, Universitas Pakuan, 2019)
Object Follower Robot is a robot that can follow the object's motion where the object will walk will be followed. The control system uses a motor driver and two dynamos to run the robot based on the color of the object detected by the Pixy CMUCAM5 camera so that it can walk following the object. This system depends on hardware and software. The hardware uses the Arduino Uno 328P as the microcontroller, the ultrasonic sensor as a distance detector, the Pixy CMUCAM5 camera as the color detector of the object, and the HX711 weight sensor as a weighing counter for shopping. As well as software using color filtering to read colors rather than objects, the results issued from color filtering are what make the conversion as a robot control system. The results of the test are to identify how the robot can follow the object, how far the robot can follow the object, and how long the robot is able to walk if the robot is turned on continuously. So it can be seen the extent to which the ability of the robot can be used